17-2 Analisis Perbandingan Biaya Riil dan Tarif Ina-Cbg’s pada Pasien Rawat Jalan Onkologi dengan Terapi Morfin Sulfat (Mst) di RSUD Arifin Achmad Provinsi Riau - Efilia Meirita; Novtafia Endri; Dewi Gulyla Hari; Rialita Lifiani (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Health service financing through the INA-CBG's (Indonesia Case-Based Groups) system aims for efficiency and transparency in the National Health Insurance (JKN) system. However, in practice, there are often discrepancies between INA-CBG's rates and the real costs incurred by health facilities, especially in oncology patients with Morphine Sulfate (MST) therapy. This study aims to analyze the comparison of real costs and INA-CBG's tariffs for oncology outpatients with morphine sulfate therapy (MST) at RSUD Arifin Achmad Riau Province. This study used descriptive observational research method with retrospective data collection obtained from medical records of oncology outpatients who received Morphine Sulfate (MST) therapy 10 mg and 15 mg tablets during the period January-March 2024. The data were analyzed by comparing the real costs incurred by the hospital with the rates paid by BPJS through the INA-CBG's system and the Mann-Whitney U test was performed. The results of the analysis showed that there was a significant difference between real costs and INA-CBG's tariffs. The average real cost of drugs (MST) was higher than the INA-CBG's tariff. The real cost of drugs that exceeded the INA-CBG's tariff amounted to 481 people, with a total cost difference (loss) of IDR 218,155,324. There was a difference between real costs and INA-CBG's rates (p = .047) and INA-CBG's rates (p = .113).